Deoxynivalenol reduces quality parameters and increases DNA damage in mice spermatozoa. (31st January 2019) - Hallaj Salahipour, Mahsa; Hasanzadeh, Shapour; Malekinejad, Hassan; Razi, Mazdak; Farrokhi‐Ardebili, Farhad
Abstract: This study was performed to investigate in vitro effects of deoxynivalenol (DON) on mice sperm quality parameters including viability, motility and DNA damages at various concentrations and exposure times. Mice spermatozoa were exposed to DON at 0, 2.5, 5 and 10 µM for 1, 3 and 6 hr, motility parameters were evaluated by computer‐assisted analysis and viability was examined by colorimetric metabolic activity assay and HOS test. DNA damage was examined by acridine orange staining, and sperm damages via lipid peroxidation pathway were determined by malondialdehyde (MDA) content measurement. DON affected sperm parameters in a concentration‐ and time‐dependent manner. In all test groups, the average path velocity and progressive motile spermatozoa were remarkably reduced. In comparison with the controls, after 1, 3 and 6 hr exposure to DON, viability of spermatozoa was reduced 25, 30 and 49% respectively. DON exposure at 10 µM for 6 hr resulted in 15% DNA damage and 2.5‐fold more MDA generation, when compared with nonexposed spermatozoa. Our data suggest that DON causes sperm quality parameters decline in concentration‐ and time‐dependent fashion, which attribute to the reduction in sperm metabolic activity and membrane integrity and equally to increase in lipid peroxidation rate and DNA damage.